17‐1: A Flat‐panel Holographic‐optical‐element System for Holographic Augmented Reality Display with a Beam Expander. Issue 1 (30th May 2018) - Zhou, Pengcheng; Li, Yan; Liu, Shuxin; Chen, Quanming; Wang, Yunfeng; Li, Sida; Liu, Yueda; Su, Yikai
Abstract : We demonstrate a compact design for holographic augmented reality displays using two holographic optical elements (HOEs). In the method, the two HOEs, which are properly set in a flat‐panel form, function as a beam expander and see‐through eyepiece simultaneously. There is no traditional optical element in the system, resulting in a compact and lightweight design. The feasibility of this design is experimentally verified.